DO SERMÃO AO SUPLÍCIO: OS CONFLITOS COM OS JESUÍTAS DURANTE O PERÍODO JOSEFINO (1755-1761) E O PROCESSO INQUISITORIAL DO PADRE GABRIELE MALAGRIDA. - Assis, Guilherme Marchiori de (2021)
The importance of correlating History and Law, trying to evaluate how a specific individual, his trajectory and his web of social relations and meanings inform us about the transformations in the relationship between secular institutions and the Church in Portugal of the Seventh Century is an arduous and rewarding task. The central character is the Italian Jesuit Gabriele Malagrida, a religious of great influence in the court of D. João V and who, after a life of missionary dedication in the colonization - having even acted as a missionary in Portuguese America - falls in disgrace before the court, Suffering a trial under the Inquisition Tribunal during the government of his successor, D. José I (1750-1777), from which he was sentenced to death. In the Kingdom, after the vicissitudes of the 1755 earthquake, Malagrida strongly criticizes Portuguese politics, and then was accused of heresy by the Inquisition, tried and sentenced to death, in a brief period of only two years (1759-1761). Condemned to the vile club and burned in Rossio Square, Lisbon, Malagrida is publicly impeached in 1761. The inquisitorial process in question, widely known by the Portuguese historiographical tradition, but little debated in the face of recent studies on the juridical and political institutions of modern Portugal, remains enveloped in multiple questions. The analysis of this document allows us to verify which political components involved the change in the Jesuit fate and how these could elucidate the relationship between individual, state and society in the period in question. It is important to emphasize that the period between the indictment and the trial (1759- 1761) coincides with the implementation of extensive transformations, characterized by the illustrated reformism of the government of the Marquis of Pombal, which, in turn, also produced important changes with regard to the Interference of the State over the Church.